Recursive identification of Wiener systems - Greblicki, Włodzimierz (Zielona Góra: Uniwersytet Zielonogórski)
A Wiener system, i.e. a cascade system consisting of a linear dynamic subsystem and a nonlinear memoryless subsystem is identified. The a priori information is nonparametric, i.e. neither the functional form of the nonlinear characteristic nor the order of the dynamic part are known. Both the input signal and the disturbance are Gaussian white random processes.
Keywords: Wiener system; system identification; recursive identification; nonparametric identification